2020
DOI: 10.1590/s1677-5538.ibju.2019.0101
|View full text |Cite
|
Sign up to set email alerts
|

Transition from open partial nephrectomy directly to robotic surgery: experience of a single surgeon to achieve “TRIFECTA”

Abstract: Introduction: Recent data suggest that robotic platform has become the most accessible minimal invasive surgery even for surgeons without previous training in laparoscopy. Laparoscopic partial nephrectomy (LPN) is a well-stablished procedure, however, with high level of complexity and long learning curve that limit its use. Objective: To describe safety, efficiency and learning curve of a single surgeon without previous experience in LPN to reach “TRIFECTA” at robot-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…In a similar study including 63 patients undergoing laparoscopic PN in T1a renal masses, Osaka et al reported that the tumor size and surgeon's learning curve were predictors of Trifecta outcomes (26). Similar to this findings, the experience of the surgeon and the size of the tumor independently predicted Trifecta outcomes (19). Another study reported that the significant predictors of Trifecta success were the tumor size, EBL, OT, robotic surgery, and high risk RENAL scores in the multivariate analysis (22).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In a similar study including 63 patients undergoing laparoscopic PN in T1a renal masses, Osaka et al reported that the tumor size and surgeon's learning curve were predictors of Trifecta outcomes (26). Similar to this findings, the experience of the surgeon and the size of the tumor independently predicted Trifecta outcomes (19). Another study reported that the significant predictors of Trifecta success were the tumor size, EBL, OT, robotic surgery, and high risk RENAL scores in the multivariate analysis (22).…”
Section: Discussionmentioning
confidence: 68%
“…The Trifecta achievement rate in previous studies has ranged between 31.6% and 87.8% ( 17 19 ). Several reasons such as surgical experience, different definitions of Trifecta, and surgical approach could have been implicated as adversely influencing the outcomes of Trifecta.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some reports show that robotic assisted NSS is safe and feasible with good short term oncological outcome, and possibility to be performed in complex cases with better results. Further experience is needed to validate RS in this scenario (32,33). Laparoscopy is still performed in a lot of countries where the access to robotic surgery is limited, even in complex cases (34).…”
Section: Discussionmentioning
confidence: 99%
“…It provides a definition of an ideal surgical outcome that includes the following three criteria: negative surgical margins, maximum renal function retention and patient recovery without complications. The use of trifecta rate as a key indicator of partial nephrectomy success has been widely reported (8)(9)(10)(11). Recently, some researchers have proposed several anatomic classification scoring systems to classify and stratify patients into different anatomic complexity groups, and allow doctors to evaluate perioperative outcomes (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%